2016
DOI: 10.1177/1052562916658688
|View full text |Cite
|
Sign up to set email alerts
|

Students as Protégés

Abstract: This study provides insight into the factors that influence satisfaction with an Internet-based practitioner-student mentoring relationship that is part of an undergraduate business school curriculum. Practitioner mentors are especially important because they can help student protégés learn the skills needed for their professional development, encourage the formation of professional networks, and enhance the protégés' satisfaction with their education. In this study, we examine a number of factors that can pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…How to select the most effective mentor is disputed. Some research showed a higher degree of satisfaction with the mentoring relationship from students who found their own mentors, as opposed to being assigned a mentor (Bear & Jones, 2017). However, without help from mentoring program matching, students may lack information on how to find a mentor or may be complacent in finding a mentor on their own.…”
Section: The Challenges Of Mentoringmentioning
confidence: 99%
See 4 more Smart Citations
“…How to select the most effective mentor is disputed. Some research showed a higher degree of satisfaction with the mentoring relationship from students who found their own mentors, as opposed to being assigned a mentor (Bear & Jones, 2017). However, without help from mentoring program matching, students may lack information on how to find a mentor or may be complacent in finding a mentor on their own.…”
Section: The Challenges Of Mentoringmentioning
confidence: 99%
“…Online mentoring provides benefits to students who may not otherwise have had access to mentors, but it also creates mentoring challenges. Only interacting online can make it more difficult to develop an effective mentoring relationship between mentors and students (Bear & Jones, 2017;Purcell, 2004). Without face-to-face, in-person communication between mentors and students, the mentor relationship may seem impersonal and other tools may need to be used to keep the mentor/student relationship progressing forward (Purcell, 2004;Rees Lewis, Harburg, Gerber, & Easterday, 2015;Sanyal & Rigby, 2017).…”
Section: The Challenges Of Mentoringmentioning
confidence: 99%
See 3 more Smart Citations